"Preparation of HY Antibody in Female Mice as a Model for Sex Preselection" - "L Andonian; MB Eslami; AA Mohammadi; J Akbarzadeh; HR Soleimanpour; DD Farhud" (Tehran University of Medical Sciences, 2001)
The aim of this sutdy is to prepare Histocompatability Y(HY) antibody in female mouse at the first phase (current study), and to separate mouse embryos with regard to their sex, to be able to obtain offsprings of disired sex, by means of HY antibody, at the second phase. Totally 421 BALB/C inbred mice were used. Antibodies were produced in females by intraperitonial injections of spleen and testis cells of neonatal male mice. The sera of females were tested by five different immunological techniques, as follows: Double gel diffusion, Counter Immunoelectrophoresis, Plain electrophoresis, Immunofluorescence and Cytotoxicity test. The first two techniques showed no positive results, but the remaining three methods proved the existence of HY antibody in sera. In electrophoresis, an increase in gamma-globulin and total globulins index, over albumin, was detected in injected mice sera. In immunofluorescence assay HY antigen was revealed on the surface of the mouse testis and spleen cells. Cytotoxicity test has been the most suitable method for detecting HY antibody. Also, the possibility to differentiate X-bearing and Y-bearing embryos could be used in prevention of X-linked diseases as well as in population control.